Design of a Thiosemicarbazide-Functionalized Calix[4]arene Ligand and Related Transition Metal Complexes: Synthesis, Characterization, and Biological Studies - Bahojb Noruzi, Ehsan; Kheirkhahi, Mahsa; Shaabani, Behrouz; Geremia, Silvano; Hickey, Neal; Asaro, Fioretta; Nitti, Patrizia; Kafil, Hossein Samadi (Frontiers in Chemistry, 2019)
In this study, we synthesized a new thiosemicarbazide-functionalized calix[4]arene L and its Co2+, Ni2+, Cu2+, and Zn2+ transition metal complexes. For characterization several techniques were employed: Fourier-transform infrared (FT-IR), 1H nuclear magnetic resonance (NMR), 13C-NMR, 15N-NMR, correlation spectroscopy (COZY), nuclear Overhauser enhancement spectroscopy (NOESY), electrospray ionization (ESI)–mass spectroscopy, scanning electron microscopy (SEM), energy-dispersive X-ray spectroscopy (EDS), and elemental analysis. To explore the capability of the thiosemicarbazide function hosted on a calix[4]arene scaffold for growth inhibition of bacteria, fungi, and cancerous tumor cells, a series of biological evaluations were performed. For L, the antimicrobial tests revealed a higher antibacterial activity against gram-positive Bacillus subtilis and a lower activity against gram-negative bacteria (Escherichia coli and Pseudomonas aeruginosa), whereas the gram-positive Staphylococcus aureus shows resistance. All examined metal derivatives show an enhancement of the antibacterial activity against gram-negative E. coli bacteria, with a more significant improvement for the Ni2+ and Zn2+ complexes. MTT assays showed a considerable in vitro anticancer activity of Co2+, Ni2+, and Cu2+ complexes against Saos-2 bone cancer cell lines. The activity is ascribable to the inorganic ions rather than calixarene ligand. Hemolysis assay results demonstrated that all compounds have high blood compatibility.